Etoricoxib-Cannabidiol Combo: Potential Role in Glioblastoma Treatment and Development of PLGA-Based Nanoparticles - Joanna Kuźmińska; Agnieszka Sobczak; Aleksandra Majchrzak-Celińska; Izabela Żółnowska; Aleksandra Gostyńska; Barbara Jadach; Violetta Krajka-Kuźniak; Anna Jelińska; Maciej Stawny (MDPI AG, 2023)
Background: Glioblastoma (GBM) is the most frequently occurring primary malignant central nervous system tumor, with a poor prognosis and median survival below two years. Administration of a combination of non-steroidal anti-inflammatory drugs and natural compounds that exhibit a curative or prophylactic effect in cancer is a new approach to GBM treatment. This study aimed to investigate the synergistic antitumor activity of etoricoxib (ETO) and cannabidiol (CBD) in a GBM cell line model, and to develop poly(lactic-co-glycolic acid) (PLGA)-based nanoparticles (NPs) for these two substances. Methods: The activity of ETO+CBD was determined using the MTT test, cell-cycle distribution assay, and apoptosis analysis using two GBM cell lines, namely, T98G and U-138 MG. The PLGA-based NPs were developed using the emulsification and solvent evaporation method. Their physicochemical properties, such as shape, size, entrapment efficiency (EE%), in vitro drug release, and quality attributes, were determined using scanning electron microscopy, diffraction light scattering, high-performance liquid chromatography, infrared spectroscopy, and differential scanning calorimetry. Results: The combination of ETO and CBD reduced the viability of cells in a dose-dependent manner and induced apoptosis in both tested GBM cell lines. The developed method allowed for the preparation of ETO+CBD-NPs with a spherical shape, mean particle size (MPS) below 400 nm, zeta potential (ZP) values from −11 to −17.4 mV, polydispersity index (PDI) values in the range from 0.029 to 0.256, and sufficient EE% of both drugs (78.43% for CBD, 10.94% for ETO). Conclusions: The combination of ETO and CBD is a promising adjuvant therapeutic in the treatment of GBM, and the prepared ETO+CBD-NPs exhibit a high potential for further pharmaceutical formulation development.